2022
DOI: 10.3390/jpm12010094
|View full text |Cite
|
Sign up to set email alerts
|

Refined Nomogram Incorporating Standing Cough Test Improves Prediction of Adjustable Trans-Obturator Male System (ATOMS) Success to Treat Post-Prostatectomy Male Stress Incontinence

Abstract: (1) Background: The adjustable transobturator male system (ATOMS) device serves to treat post-prostatectomy incontinence, as it enhances residual urinary sphincteric function by dorsal compression of the bulbar urethra. We investigated the clinical parameters affecting continence recovery using this device and developed a decision aid to predict success. (2) Methods: We reviewed consecutive men treated with first-time ATOMS for post-prostatectomy incontinence from 2014 to 2021 at our institution. Patient demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…MSIGS has also been shown to correlate strongly with the 24-hour pad weight, which has a high predictive value for sling outcomes (18-21) (Table 1) (1,22). While there is currently no standardized cutoff for incontinence procedure selection based on the 24-hour pad weight test, Kumar et al found that slings have significantly lower efficacy for patients with pad weight ≥400 g which correlates closely to MSIGS score of three (1,15,22,23).…”
Section: Validity Of Msigsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSIGS has also been shown to correlate strongly with the 24-hour pad weight, which has a high predictive value for sling outcomes (18-21) (Table 1) (1,22). While there is currently no standardized cutoff for incontinence procedure selection based on the 24-hour pad weight test, Kumar et al found that slings have significantly lower efficacy for patients with pad weight ≥400 g which correlates closely to MSIGS score of three (1,15,22,23).…”
Section: Validity Of Msigsmentioning
confidence: 99%
“…; Feldkirch, Austria) with an accuracy of 82.21%. Moreover, the ATOMS trial found MSIGS combined with a pad test (mean 24-hour pad weight over 3-day period) was superior to pad test alone as a predictor of success (AUC 82.36 vs. 77.43) (22). Abramowitz et al failed to find a correlation between MSIGS and success rates (defined by 1 or less PPD at last follow-up) for the Virtue male quadratic sling (Coloplast, Humlebaek, Denmark), however this study deviated from our published protocol as the SCT was performed immediately following cystoscopic bladder filling (29).…”
Section: Limitationsmentioning
confidence: 99%
“…The adjustable trans-obturator male system (ATOMS) exerts as a sling that reinforces the urethral sphincter by compression of the bulbar urethra without the need for manipulation by the patient. However, to exert its role ATOMS requires some residual sphincteric function [ 12 ].…”
Section: Post-prostatectomy Incontinence (Ppi) Treatment Optionsmentioning
confidence: 99%
“…This device allows the bulbar urethra to be compressed only on one side and not circumferentially like the AUS. Ventral urethral compression can be increased after surgery by percutaneous injection of sterile saline solution into the port without intervention [ 11 , 12 ]. A prospective comparative study between the ATOMS and the AUS confirmed equivalent efficacy and patient satisfaction results, with a lower revision rate and higher durability for ATOMS [ 10 ].…”
Section: Development and Evolution Of The Atoms Devicementioning
confidence: 99%
“…Other options such as retro-urethral fixed bulbar slings are preferred for the first-line treatment of mild-to-moderate incontinence after radical prostatectomy in the absence of radiation, and the artificial urinary sphincter (AUS) is probably the best option for severe SUI without residual sphincteric function [ 2 ]. However, choosing the best treatment option for a particular patient can be a difficult task [ 3 ].…”
Section: Introductionmentioning
confidence: 99%